2013
DOI: 10.3892/etm.2013.1273
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer of human neuregulin-1 attenuates ventricular remodeling in diabetic cardiomyopathy rats

Abstract: Neuregulin-1 (NRG-1) is a cardioactive growth factor released from endothelial cells. However, the effect of NRG-1 on ventricular remodeling in diabetic cardiomyopathy (DCM) remains unclear. The aim of the present study was to investigate the pathophysiological role of NRG-1 in a rat model of DCM. Rat cardiac microvascular endothelial cells (CMECs) were transfected with human NRG-1 (hNRG-1) lentivirus. The hNRG-1 medium was utilized to culture rat cardiomyocytes. The cardiomyocytes were counted with a hemacyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
4
5
1
Order By: Relevance
“…In a chronic stabilized condition, NRG-1 may induce cardiomyocyte mitosis and promote myocardial regeneration (3). Also, protection against diabetic cardiomyopathy in type 1 diabetes has been described (22,23). Consistent with previous data, rhNRG-1 reversed cardiac MHC␣ downregulation and enhanced LV eNOS phosphorylation, presumably contributing to improved contractile function and reduced LV remodeling (22,24).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In a chronic stabilized condition, NRG-1 may induce cardiomyocyte mitosis and promote myocardial regeneration (3). Also, protection against diabetic cardiomyopathy in type 1 diabetes has been described (22,23). Consistent with previous data, rhNRG-1 reversed cardiac MHC␣ downregulation and enhanced LV eNOS phosphorylation, presumably contributing to improved contractile function and reduced LV remodeling (22,24).…”
Section: Discussionsupporting
confidence: 74%
“…Consistent with previous observations, phosphorylation of LV eNOS in rhNRG-1-treated mice was enhanced, both in apoE Ϫ/Ϫ control and in apoE Ϫ/Ϫ STZ mice ( Fig. 1D) (22).…”
Section: Nrg-1 Prevents Diabetes-induced Cardiac Dysfunction In Apoe supporting
confidence: 80%
See 1 more Smart Citation
“…So these findings indicate HCMECs and SMC can participate in both autocrine and paracrine regulation via NRG-1/ErbB signaling, an important potential mechanism for regulation of vascular responses. ErbB2 and ErbB4 are expressed in cardiomyocytes, the crosstalk between endothelial cells and cardiomyocytes via this pathway can have profound effects on myocardial function and survival (23).…”
Section: Discussionmentioning
confidence: 99%
“…Till now, NRG1 is the most extensively characterized of the NRGs family, which has a key role in neural and cardiac development. NRG1 can not only modulate synaptic plasticity, but also stimulate the proliferation, survival and motility of a number of different cell types through binding to ErbB tyrosine kinase [2][3][4] . It has also shown that NRG1 is required for the development of the peripheral nervous system.…”
Section: ■ Introductionmentioning
confidence: 99%